(untitled) (Journal of Hama University, 2026)
The aim of this study was to identify differences between children with autism spectrum disorder and their peers with Down syndrome in the most important psychomotor skills, and to identify differences between the average scores of children with autism and children with Down syndrome on psychomotor skills scales according to age (4-5 years, 6-7 years), and To identify the level of psychomotor skills among a sample of children with autism spectrum disorder and their peers with Down syndrome in special education centers in Lattakia, using the descriptive approach. The sample included (20) boys and girls with autism spectrum disorder and Down syndrome. To achieve the research objective. Two scales were relied upon in this field, namely (Dayton Scale of Perceptual-Sensorimotor Abilities for children aged (4-5) years - Haywood Scale of Perceptual-Sensorimotor (5-7) years). The results of the research showed a weak level of psychomotor skills among children with Down syndrome and children with autism in general, and the absence of statistically significant differences between the average scores of children with autism and children with Down syndrome on psychomotor skills scales. A statistically significant difference was found between the average scores of children (children with autism and children with Down syndrome) on psychomotor skills scales according to the age variable (4-5) years, (6-7) years, in favor of children aged (6-7) years. The study presented several proposals, the most important of which are: conducting further studies and research to identify the impact of psychomotor skills on various aspects of development in children with Down syndrome and autism, and preparing specialists in the field of psychomotor education to work with children with disabilities.